2016
DOI: 10.1073/pnas.1524687113
|View full text |Cite
|
Sign up to set email alerts
|

Extreme cellular adaptations and cell differentiation required by a cyanobacterium for carbonate excavation

Abstract: Some cyanobacteria, known as euendoliths, excavate and grow into calcium carbonates, with their activity leading to significant marine and terrestrial carbonate erosion and to deleterious effects on coral reef and bivalve ecology. Despite their environmental relevance, the mechanisms by which they can bore have remained elusive and paradoxical, in that, as oxygenic phototrophs, cyanobacteria tend to alkalinize their surroundings, which will encourage carbonate precipitation, not dissolution. Therefore, cyanoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…It is likely that chip removal processes utilize products from the dissolution to contract their tissue and move the chip up from the boring pit into an excurrent canal. Work on phototrophic cyanobacteria showed that microbial excavation was achieved by transcellular Ca 2+ transport (Garcia-Pichel, 2006;GarciaPichel et al, 2010;Guida and Garcia-Pichel, 2016). We tentatively suggest that the excess in Ca 2+ derived from the dissolution in CaCO − 3 may be used by sponges to contract a conductive pathway, similarly to how muscle cell contract when triggered by an increase in intracellular Ca 2+ (Sommerville and Hartshorne, 1986).…”
Section: Effects Of Pco 2 and Eutrophication On Bioerosionmentioning
confidence: 69%
See 1 more Smart Citation
“…It is likely that chip removal processes utilize products from the dissolution to contract their tissue and move the chip up from the boring pit into an excurrent canal. Work on phototrophic cyanobacteria showed that microbial excavation was achieved by transcellular Ca 2+ transport (Garcia-Pichel, 2006;GarciaPichel et al, 2010;Guida and Garcia-Pichel, 2016). We tentatively suggest that the excess in Ca 2+ derived from the dissolution in CaCO − 3 may be used by sponges to contract a conductive pathway, similarly to how muscle cell contract when triggered by an increase in intracellular Ca 2+ (Sommerville and Hartshorne, 1986).…”
Section: Effects Of Pco 2 and Eutrophication On Bioerosionmentioning
confidence: 69%
“…carbonate dissolution, photosynthesis must therefore supply a high fraction of the energetic costs of the bioerosion process which may include ATP usage for active Ca 2+ and/or active proton pumping (Guida and Garcia-Pichel, 2016). Higher rates during the day at low and ambient pCO 2 indicate that the benefit of acquired energy from photosynthetic activity FIGURE 6 | Net respiration rates (Resp net ) during the day (dark orange), dark respiration rates (dark Resp) during the night (light orange) and gross photosynthesis (P gross ) of the holobiont (sponge + symbionts) ± SEM for each pCO 2 and eutrophication scenario.…”
Section: Respiration Photosynthesis and Changes In Chemical Bioerosimentioning
confidence: 99%
“…Among cyanobacteria, the differentiated cells called calcicytes, observed in the filamentous euendolithic cyanobacterium Mastigocoleus testarum, have been measured to contain 100 fmol of Ca per cell, which measured ~1 × 10 3 μm 3 (Guida & Garcia‐Pichel, ). This represents 20 mg of Ca per g of dry weight, a value similar to that estimated for cyanobacteria forming intracellular ACC (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Endolithic bacteria bore into carbonate substrate through dissolution facilitated by uptake, transport and eventual release of calcium ions at the distal end of multicellular cyanobacterial trichomes (Fig. 3) [50, 51]. Increased concentration of free calcium ions at the surface of the stromatolite may promote calcium carbonate precipitation [31].…”
Section: Resultsmentioning
confidence: 99%
“…Increased concentration of free calcium ions at the surface of the stromatolite may promote calcium carbonate precipitation [31]. Certain genes are upregulated during this boring activity, including key genes encoding calcium ATPases and calcium-binding proteins [51, 52]. We identified an incredible 1 182 gene copies encoding calcium-binding proteins and 315 calcium ATPases in the putative genomes of bacteria from Cape Recife and Schoenmakerskop stromatolites.…”
Section: Resultsmentioning
confidence: 99%